Respostas

2014-07-22T17:50:42-03:00
6x² -12x = 0

Δ=(-12)²-4.6.0
Δ=144

x'=-(-12)+
√144/2.6=(12+12)/12=24/12=2
x'=-(-12)-√144/2.6=(12-12)/12=0/12=0
pedro da pra tu faser desse jeito ? 3x² - 27 = 0
a = 3
b = 0
c = - 27
/\ = b² - 4ac
/\ = 0² - 4 * 3 * (- 27)
/\ = 0 + 324
/\ = 324
x = - b + V¨¨¨¨¨¨/\
--------------------
2a
x = - 0 + V¨¨¨324
--------------------
2 * 3
x = - 0 + 18
------------
6
x' = - 0 + 18
6
x' = 18 : 6
x' = 3

x" = - 0 - 18
6
x" = - 18 : 6
x" - 3
Resposta: (3, - 3)
A melhor resposta!
2014-07-22T17:52:04-03:00
Essa é uma equação de 2º grau incompleta, ou seja, C=0

Calculando Δ:

Δ = b²-4ac
Δ= 12² - 4.6.0
Δ = 144

x = \frac{-b +-  \sqrt{delta}  }{2a}

x = \frac{-12+12}{2.6} = 0

x' = \frac{-12 - 12}{2.6} =  \frac{-24}{12} = -2

S = {0, -2 }

2 5 2